Assessment of the Prevalence of Symptoms in Patients Under Institutional Isolation in COVID-19 Pandemic in India - Kumar, Sanjeev (Indian J Palliat Care, 2020)
OBJECTIVE: To understand the trend of prevalence of symptoms of coronavirus disease 2019 (COVID-19) pandemic, some studies have been conducted outside India, but for Indian patients, there is no such study available. Therefore, this study was designed to analyze the trends of symptoms in Indian patients during COVID-19 pandemic. METHODS: A retrospective study was conducted on 100 patients (73 males, 24 females, and 3 transgenders) admitted under institutional isolation at a tertiary care center in India using a self-designed survey-based questionnaire. A descriptive analysis of results done based on age and sex. RESULTS: COVID incidence recorded is high in male (73%) as compared to female (24%), yet female patients have a higher prevalence of symptoms as compared to male patients. CONCLUSION: Male patients are more as far as COVID incidence is concerned, while female patients show high prevalence of symptoms as compared to male patients. Patients presenting with COVID-positive report suffer a significant burden of symptoms, and timely recognition of symptoms and their management can significantly reduce morbidity and mortality due to COVID-19.